Specialist or Nonspecialist Physical Education Teachers in Ontario Elementary Schools: Examining Differences in Opportunities for Physical Activity - Faulkner, Guy E.J.; Dwyer, John J.M.; Irving, Hyacinth; Allison, Kenneth R.; Adlaf, Edward M.; Goodman, Jack (Alberta Journal of Educational Research, 2008)
Research supports the position that specialists are the preferred providers of physical education in elementary (primary) school settings. We examined whether specialists delivered more physical education lessons and provided greater opportunities for moderate and vigorous physical activity and whether barriers to curricular and extracurricular physical activity opportunities in Ontario elementary schools differed for specialist and nonspecialist teachers. Using a cross-sectional design, a questionnaire was mailed to key informants in 599 randomly selected elementary schools in Ontario, yielding an 85% response rate. Most physical education in Ontario elementary schools is delivered by nonspecialists (63%). No self-reported differences were found between specialists and generalist teachers in the number of physical education lessons delivered per week, the minutes per physical education class, or in the amount of reported moderate or vigorous physical activity in lessons. Compared with specialists, respondents in schools in which generalist teachers taught PE perceived lack of training as a greater barrier to delivering physical education. Given the importance of subject knowledge in teaching effectively, there is still need to advocate for specialist physical education teaching in elementary schools. However, concerns about teaching specialism may be secondary to broader and more complex factors surrounding the delivery of physical education in elementary schools.